Effects of different doses of testosterone on gonadotropins, 25-hydroxyvitamin D3, and blood lipids in healthy men - Gårevik N; Rane A; Björkhem-Bergman L; Ekström L (Dove Medical Press, 2014)
Nina Gårevik, Anders Rane, Linda Björkhem-Bergman, Lena Ekström Division of Clinical Pharmacology, Department of Laboratory Medicine, Karolinska Institutet, Karolinska University Hospital, Stockholm, Sweden Aims: To study the effect and time profile of different doses of testosterone enanthate on the blood lipid profile and gonadotropins. Experimental design: Twenty-five healthy male volunteers aged 27–43 years were given 500 mg, 250 mg, and 125 mg of testosterone enanthate as single intramuscular doses of Testoviron® Depot. Luteinizing hormone (LH), follicle-stimulating hormone (FSH), blood lipid profile (total cholesterol, plasma [p-] low-density lipoprotein, p-high-density lipoprotein [HDL], p-apolipoprotein A1 [ApoA1], p-apolipoprotein B, p-triglycerides, p-lipoprotein(a), serum [s-] testosterone, and 25-hydroxyvitamin D3) were analyzed prior to, and 4 and 14 days after dosing. Testosterone and epitestosterone in urine (testosterone/epitestosterone ratio) were analyzed prior to each dose after a washout period of 6–8 weeks. Results and discussion: All doses investigated suppressed the LH and FSH concentrations in serum. LH remained suppressed 6 weeks after the 500 mg dose. These results indicate that testosterone has a more profound endocrine effect on the hypothalamic–pituitary–gonadal axis than was previously thought. There was no alteration in 25-hydroxyvitamin D3 levels after testosterone administration compared to baseline levels. The 250 and 500 mg doses induced decreased concentrations of ApoA1 and HDL, whereas the lowest dose (125 mg) did not have any effect on the lipid profile. Conclusion: The single doses of testosterone produced a dose-dependent increase in serum testosterone concentrations together with suppression of s-LH and s-FSH. Alterations in ApoA1 and HDL were observed after the two highest single doses. It is possible that long-time abuse of anabolic androgenic steroids will lead to alteration in vitamin D status. Knowledge and understanding of the side effects of anabolic androgenic steroids are important to the treatment and care of abusers of testosterone. Keywords: anabolic androgenic steroids, testosterone, gonadotropins, vitamin D, blood lipids, abuse